Phosphoramidate analogues of DNA: synthesis and thermal stability of heteroduplexes. - Froehler, B (1988)
The deoxyoligonucleotide 5' AATCGGGCATGGATT (15-mer) was synthesized containing 12 phosphoramidate linkages derived from 2 primary and 2 secondary amines. The oligonucleotides were purified by reverse phase HPLC and characterized by PAGE. The thermal stability of the duplexes derived from these compounds, when hybridized to the complementary diester linked oligomer, were determined and compared to the diester and methanephosphonate oligomer. The results indicated that all analogue oligomers form less stable duplexes then the diester oligomer. A large difference was observed between primary and secondary amine derived phosphoramidates.